A political‐economic theory of relevance: Explaining climate change inaction. (23rd August 2019) - Gunderson, Ryan; Stuart, Diana; Houser, Matthew
Abstract: Why have societies failed to effectively respond to climate change? We address the question of climate change inaction by (1) examining how an unambiguously ominous report about climate change (IPCC 2018) was made palatable by news media and (2) explaining why climate change is typically unthematized in everyday life. Drawing on Adorno and Schutz, we develop a political‐economic theory of relevance. The imperative to accumulate capital is not only a social‐structural reality but also shapes why particular facts are regarded as relevant in experience (topical relevance) as well as how relevant material is interpreted (interpretative relevance) and acted toward (motivational relevance). Applying this framework, we (1) argue that media popularizations of the IPCC's dire Global Warming of 1.5°C (2018) are constituted by relevance systems conditioned by a capitalist social context and (2) strengthen Ollinaho's (2016) Schutzian explanation for climate change inaction by examining how productive relations and the culture industry perpetuate climate change irrelevance in everyday life. Schutz's framework helps conceptualize the intricacies of ideology and, when revised with Adorno's sociology, shines new light on an old question: the relations between social conditions and knowledge.